Implementasi Model Project-Based Learning untuk Meningkatkan Hasil Belajar Siswa di Sekolah Menengah Kejuruan - Putra, Alzico Tri; Yanto, Doni Tri Putra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This study aims to determine the effectiveness of the Project-based Learning model and student learning outcomes after implementing learning using the PjBL model in the Electrical Lighting Installation subject class XI TITL at SMK Negeri 1 Padang. Student learning outcomes are still low which is caused by learning factors that are still teacher-centered, thus affecting student learning outcomes in the cognitive. Therefore, it is necessary to apply a project-based learning model to find out how effective this learning model is on student learning outcomes. This research uses a type of experimental research with a pre-experimental method with a one-group pretest-posttest design. The object of this research is the project-based learning model and the effectiveness of its application on student learning outcomes in the subject of electrical lighting installation. The subject of this research was class XI TITL SMK Negeri 1 Padang. The instruments used in this research were tests. Based on the average posttest scores it is in the high category. Therefore, the application of the project-based learning model in the Electrical Lighting Installation subject is said to be effective because the increase in student learning outcomes the percentage of students the classical completeness score, and effect size are included in the large category.